Optimal allocation and sizing of electrical substations using the crow search algorithm - Paixão Matos, Arthur do Carmo; Bravin Donadel, Clainer (Latin American Journal of Energy Research, 2024)
The continuous increase in global demand for electrical energy has driven significant momentum in the energy sector worldwide. As highlighted in the latest report by the International Energy Agency (2022), the demand for electricity in 2021 reached an impressive 24,700 TWh, marking a 6% increase compared to the previous year, representing the largest growth since 2010. This context underscores the need for a robust and reliable electrical distribution system capable of meeting this growing demand without compromising service due to potential system inadequacies. In this regard, this paper proposes a novel approach to addressing the challenge of optimal allocation and sizing of electrical substations in distribution systems, based on the intelligence of crows, through the Crow Search Algorithm (CSA). Additionally, the developed method also organizes the connection of electrical substations to load centers. The primary objective is to minimize the overall costs of the substation allocation and sizing project, considering a set of technical and operational objectives and constraints. The metaheuristic tests were conducted on a distribution system presented in the literature, which includes 38 load centers and 6 existing substations, allowing for the establishment of different application scenarios of the method. The results indicate that the CSA is a promising method for solving the problem of optimal allocation and sizing of electrical substations.